2013
DOI: 10.1007/978-1-4471-5301-6_10
|View full text |Cite
|
Sign up to set email alerts
|

User Interaction Templates for the Design of Lifelogging Systems

Abstract: A variety of life-tracking devices are being created to give opportunity to track our daily lives accurately and automatically through the application of sensing technologies. Technology allows us to automatically and passively record life activities in previously unimaginable detail, in a process called lifelogging. Captured materials may include text, photos/video, audio, location, Bluetooth logs and information from many other sensing modalities, all captured automatically by wearable sensors. Experience su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…[Lar13] propose quantified self (QS) Spiral an interactive visualization technique that aims to capture the quantified self-data and let the user explore those recurring patterns. [Hop13] present different visualization techniques like Comic-book style Visual diary inspired by the squarified treemap pattern, timeline, master detailed having the appearance of a thumbnail gallery, a social interaction radar graph and a activity yearly calendar. [Dua17] investigate in virtual reality by realizing a virtual reality lifelog prototype.…”
Section: Multimodal Visualizationmentioning
confidence: 99%
“…[Lar13] propose quantified self (QS) Spiral an interactive visualization technique that aims to capture the quantified self-data and let the user explore those recurring patterns. [Hop13] present different visualization techniques like Comic-book style Visual diary inspired by the squarified treemap pattern, timeline, master detailed having the appearance of a thumbnail gallery, a social interaction radar graph and a activity yearly calendar. [Dua17] investigate in virtual reality by realizing a virtual reality lifelog prototype.…”
Section: Multimodal Visualizationmentioning
confidence: 99%
“…vast amount of visual data may need to be aligned to GPS data) compared to the numerical fitness data, and requires careful consideration on how to present and summarize such information. In relation to the user interaction in lifelogging, Hopfgartner et al [3] have outlined various design templates that may help to support different visualization schemes and perhaps invoke further research efforts in this direction. The authors have suggested that visual diaries should summarize a user's day, a comic-book style interface should be used when the screen space is limited (handheld devices) and a master-detailed interface should be used to facilitate lifelog image exploration.…”
Section: Background Workmentioning
confidence: 99%
“…Despite the growing number of studies using lifelogging such as with wearable cameras, there has been little consideration on how to visualize and present the lifelogs in a user-friendly yet meaningful way. A handful of the existing works [3,4] have proposed a number of design guidelines and visualization techniques to present the lifelog images, but they have not reported any user studies to evaluate the effectiveness of the proposed techniques. It is our conjecture that visualization of lifelog images is a necessary aspect, which must be considered, when designing lifelogging tools to enrich the user experience and support their needs.…”
Section: Introductionmentioning
confidence: 99%
“…In [8] Viégas and Wattenberg illustrate how such techniques can be seized by artists for artful designs, including project Last Clock, by Jussi Angesleva and Ross Cooper that is inspiring for the FlanoGraphs. In [9] Hopfgartner et al discuss user interface design cues for lifelogging applications. Such mobile augmented reality (MAR) applications yield at providing sensing, logging and displaying on the same device.…”
Section: Interfaces and Presentation Enginesmentioning
confidence: 99%